Life and Times of David - Mackintosh, Charles Henry (Auckland : The Floating Press, 2013)
A wise king and, by some accounts, a distant ancestor of Jesus, David is one of the most compelling figures depicted in the Bible. In this thoughtful and comprehensive volume, theologian Charles Henry Mackintosh provides rich historical context for gaining a deeper understanding of David and his important contributions to Christianity.
Title; Contents; Introduction; Chapter I -- David Anointed; Chapter II -- The Valley of Elah; Chapter III -- The Cave of Adullam; Chapter IV -- Nabal and Abigail; Chapter V -- Ziklag; Chapter VI -- The Return of the Ark; Chapter VII -- David's House and the House of God; Chapter VIII -- The Conspiracy; Chapter IX -- The Song and Last Words; Endnotes
Description based upon print version of record.
Keywords: Christianity; Jesus Christ; Religion; David, -- King of Israel; RELIGION / Christian Life / General; Electronic books